MIRERC 078/2025: Political Participation Among Youth in Kenya - Dr. Scovia Aweko; Antony Mutwiri (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Executive summary Over the past two decades, leaderless protest movements have gained prominence, effectively mobilizing large numbers of young people across demographic and geographic divides. Commonly referred to as #hashtag protests, these movements are organized primarily through social media and unified by short, memorable hashtags that convey collective grievances and demands. Despite their decentralized nature, they have been met with widespread state repression, ranging from police beatings, arrests, and abductions to the use of live ammunition. The #EndSARS protests in Nigeria illustrate this clearly, as peaceful demonstration against police brutality ended with the army opening fire on protesters at the Lekki Toll Gate following a government-imposed curfew. While existing scholarship has focused largely on mobilization through formal, hierarchical organizations, less attention has been given to how leaderless movements organize for collective action. This study addresses that gap by examining how mobilizers within hashtag protests interpret pivotal protest events and leverage those meanings to sustain participation. Building on social movement theory and drawing from literature on critical junctures, the research explores the strategies that enable decentralized protests to maintain momentum, shape narratives, and advance collective action despite repression.